The Situation of Animal Product Consumption and Preferences among Final-Year Students at Firat University, Faculty of Veterinary Medicine - Gokhan, Emin Ertan (Medwell Online, 2013)
This study was aimed at determining the situation of animal product consumption and preferences among final-year students at Firat University, Faculty of Veterinary Medicine and defining the factors influential on their preferences. The material of the study, conducted during the 2010-2011 academic year, was comprised of data collected by a survey study of 105 final-year students. The results of the survey study demonstrated that the monthly individual income of 55.24% of the participants was below 500 TL and that those with a monthly individual food expenditure below 250 TL accounted for 75.2% of the participants. It was found that the meat consumption of these students depended primarily on poultry meat and that their red meat preference was in favour of beef and veal. The average monthly milk consumption of the participants was 1.9 L.
Keywords: Student income; animal product; consumption preferences; beef; veal